2020
DOI: 10.3390/metabo10070270
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Alterations Associated with Cesium-137 Internal Emitter Delivered in Various Dose Rates

Abstract: Our laboratory and others have use radiation metabolomics to assess responses in order to develop biomarkers reflecting exposure and level of injury. To expand the types of exposure and compare to previously published results, metabolomic analysis has been carried out using serum samples from mice exposed to 137Cs internal emitters. Animals were injected intraperitoneally with 137CsCl solutions of varying radioactivity, and the absorbed doses were calculated. To determine the dose rate effect, serum samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Similar alterations to the microbiome (especially, members of the bacterial taxa Lachnospiraceae and Enterococcaceae) and metabolites of potential microbial origin (including tryptophan-derived indoles) have been reported in the plasma of humans surviving ionizing radiation exposure. , Studies have also confirmed alterations in tryptophan/indole metabolism in low-dose uranium radiation exposure studies . Studies on serum and plasma have been reported at a low dose of radiation (e.g., 4 Gy) or urine (with a total dose of radiation between 5 and 10 Gy over a 30 day period) . Metabolomic studies examining the impact of bone marrow failure-inducing doses of radiation have also been published to document the effect on mice exposed to a higher radiation dose range (5–11 Gy).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar alterations to the microbiome (especially, members of the bacterial taxa Lachnospiraceae and Enterococcaceae) and metabolites of potential microbial origin (including tryptophan-derived indoles) have been reported in the plasma of humans surviving ionizing radiation exposure. , Studies have also confirmed alterations in tryptophan/indole metabolism in low-dose uranium radiation exposure studies . Studies on serum and plasma have been reported at a low dose of radiation (e.g., 4 Gy) or urine (with a total dose of radiation between 5 and 10 Gy over a 30 day period) . Metabolomic studies examining the impact of bone marrow failure-inducing doses of radiation have also been published to document the effect on mice exposed to a higher radiation dose range (5–11 Gy).…”
Section: Introductionsupporting
confidence: 55%
“…Metabolomic studies examining the impact of bone marrow failure-inducing doses of radiation have also been published to document the effect on mice exposed to a higher radiation dose range (5–11 Gy). These identified a significant enrichment in purine metabolism, tricarboxylic acid cycle, fatty acids, acyl-carnitines, and amino acids in the spleen of animals upon early perturbations with γ irradiation . Despite several studies focusing on plasma, to the best of our knowledge, dose–response studies focusing on plasma, blood, and multiple organs have not been published yet, making it difficult to appreciate system-wide responses to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…While the above studies demonstrated several biophysiological consequences of LDR IR exposure, they used a static dose rate that does not replicate the biokinetics of internally deposited 137 Cs associated with nuclear fallout. To address the variable dose rate encountered in a realistic exposure scenario from internal deposition, our group previously designed a set of experiments that used 137 CsCl (aq) and 90 SrCl 2(aq) injections in mice and demonstrated several downstream perturbations at the transcriptomic and metabolomic levels. However, inherent challenges associated with this design, such as the need for specialized facilities and instrument contamination from radioactive biofluids, limits the use of its application and does not effectively model external fallout exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the top candidates from both of these disciplines can be combined into a single rapid multiplex assay useful in dose reconstruction and be effective irrespective of the complex nature associated with radiation exposures (e.g., dose rate), combined injury, genetic predisposition, etc. A particular recent focus of our group has been elucidating the effects of dose-rate on biofluid signatures and its potential to alter predictive model power [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Third, internal emitter radiation, of primary concern the radioisotope 137 Cs, can continue for weeks if chelating agents are not used [11]. As our previous research addressed effects of internal emitters or nuclear fallout on dose reconstruction [5,[7][8][9]12], further research is also needed in the VHDR range.…”
Section: Introductionmentioning
confidence: 99%